PENGARUH HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KARTU PERDANA XL PADA MAHASISWA FAKULTAS ILMU ADMINISTRASI UNIVERSITAS HALU OLEO KENDARI - anwar, eka fitriana (Business UHO: Jurnal Administrasi Bisnis, 2018)
The Influence of Price and Promotion on Purchasing Decision of XL Primary Card (In Student of Halu Oleo Kendari University Administration Science Faculty). Supervisor 1: Rahman and Supervisor II: SahrunThe purpose of this research is to know and mendkrepsikan influence of price and promotion to decision of purchasing XL starter card (On Student of Faculty of Administrative Sciences Halu Oleo Kendari University)The data collection techniques that are used in this study are faculty students of administration sciences that use XL starter card as many as 39 respondents. The sample in this research using porposive sampling technique. Then the data obtained in the analysis quantitatively through multiple linear regression analysis The result of research shows that: (1) Price influence to purchasing decision, (2) Promotion influence to purchasing decision (3) Price and promotion simultaneously influence to purchasing decision. Thus it can be concluded that the price and promotion significantly influence both the persial or simultaneous to the purchase decision.Keywords: Price, Promotion, and Purchase Decision